Three Inferior Oblique Weakening Procedures for Management of Mild Hypertropia in Unilateral Superior Oblique Muscle Palsy - Hajar Farvardin; Fatemeh Ebrahimi; Mohammadreza Talebnejad; Hadi Farvardin; Alireza Attar; Majid Farvardin (Journal of Ophthalmic & Vision Research)
Purpose: To investigate the surgical outcomes of three different types of inferior oblique muscle weakening procedures in patients with mild hypertropia due to unilateral superior oblique muscle palsy. Methods: We reviewed surgical data of patients aged >30 years with unilateral superior oblique palsy. The patients were categorized into three groups in terms of the surgical procedure: inferior oblique myectomy (IOM), inferior oblique recession (IOR), and inferior oblique disinsertion (IOD). Patients with preoperative hypertropia of 6 to 10 prism diopters (PD) were selected as mild cases for further comparison. Demographic data, preoperative and postoperative deviations in the primary position, contralateral gaze, contralateral elevation gaze, and ipsilateral tilt were considered for analysis. Complete success was defined as achieving postoperative orthotropia in addition to the resolution of diplopia and head tilt. Results: A total of 82 patients with an average age of 11.8 years were included in this study. The male-to-female ratio was 1.27, and the most common cause of palsy was congenital (89%). Fifty-six patients were treated with IOM, thirteen with IOR, and thirteen with IOD. The mean hypertropia correction was significantly better in the IOM group (9.1 PD) than in the IOR (7.1 PD) and IOD (7.5 PD) groups. Complete success was achieved in 80.3% of the IOM group, 69.2% of the IOR group, and 84.6% of the IOD group. The reoperation rate was 1.7% in the IOM group and 7.6% in the IOR group. Conclusion: Compared to IOR and IOD procedures, IOM was more effective in correcting hypertropia in patients with inferior oblique muscle overaction and mild hypertropia secondary to unilateral superior oblique palsy.